Cadence adaptations of double poling technique in elite cross-country skiers - Lindinger, S. J.; Holmberg, H. C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
During the last decade, double poling (DP) became a main classical technique in cross-country (XC) ski racing. A recent study analyzed speed influence on biomechanics of DP and found increases in poling frequency, cycle length, peak pole force, flexion and extension ranges of motion and angular velocities in arm and leg joints and decreases in poling time and time to peak pole force (Lindinger et al, 2009). Cadence and its influence on exercise is well investigated in different cyclical activities like running, race walking, swimming, etc. (Marais et al. 2003) but rarely anaylzed in XC skiing (Millet et al. 1998). The purpose of a bigger project was to answer the question "Does an optimal cadence exist and which factors determine the choice of cadence?". The aim of the current biomechanical study was to analyze the influence of different cadences on three submaximal velocities during DP. 10 elite XC skiers roller skied using DP at three given cadences (40, 60 and 80 pole thrusts per min [t •min-1]) performed at three submaximal treadmill velocities (12, 18, 24 km•h-1). Joint angles (Noraxon, Germany), EMG activity of triceps brachii and axial pole forces (strain gauge system) were measured by Noraxon-System (Germany). Repeated ANOVA were calculated to analyze changes in all variables across cadences at all speeds (statistical level P<0.05). Poling time decreased with higher cadence (P<0.05) and reached critically short values of ~0.2 s at 80 t •min-1 at 24 km•h-1 compared to ~0.3 s at 40 t •min-1. Relative poling and recovery time (% cycle time) increased and decreased with higher cadences (all P<0.05) showing minima and maxima of ~20 and ~80% cycle time at the lowest cadence of 40 t •min-1. Peak pole force and impulse of pole force decreased with increasing cadence leading to smaller power outputs per cycle at high DP cadences (all P<0.05). Heel lift, elbow, hip and knee joint flexion and extension ranges of motion and angular velocities decreased with higher cadences at all speeds (all P<0.05). Triceps pre-activation and MPF increased with higher cadences whereas average EMG during flexion and extension phase decreased (all P<0.05). Today`s top skiers adapt to higher cadence by decreasing absolute and increasing relative poling times, decreasing forces and impulses of forces, upper and lower body joint motions and changing EMG activity. In contrast cycling the change of joint kinematics is unique and might affect work economy during DP at different cadences. Anthopometry, technique and muscle quality might play a crucial role concerning the question "Which is the optimal cadence during DP in XC skiing?". Further investigations will be necessary to answer these important questions. Lindinger SJ, Stöggl T, Müller E, Holmberg HC. (2009). Control of speed during the double poling technique performed by elite cross-country skiers. Med Sci Sports Exerc. 41(1):210-20. Marais G, Pelayo P. (2003). Cadence and exercise: physiological and biomechanical determinants of optimal cadences-practical applications. Sports Biomech. 2(1):103-32. Review.